Job Satisfaction as Mediator: The Role of Leadership Style and Organizational Culture on Employee Performance in Budget-Hotel - Ahmad Armaendi Makawi; Bima Resi Pahlawan; Dhiva Andika; Sekar Wulan Prasetyaningtyas (Journal of Research in Business, Economics, and Education, 2020)
Budget hotels around the world have developed rapidly in the last few decades. Good hotel services and provision are urgently needed by Indonesia because Indonesia's growing tourism industry requires a maximum level of service. Currently the trend in tourism which is very common in the world is to travel on a low-budget, backpacker, or staycation. The consumer behavior of the tourism industry has changed the tourism business. Employee performance is very important for any organization, because organizational success depends on the creativity, innovation, satisfaction and commitment shown by its employees. Employee performance is more significant in this industry because employees have direct contact with customers as well as hotel industry employees who provide services to their customers. The decline in performance is an important issue in research on the hotel industry in Indonesia, because tourism is the leading sector and has experienced the largest increase. In some Asian countries such as Indonesia, tourism is a key sector in increasing the income of the population. Improved services in hotel research should be carried out, especially for budget hotels which have limited services. This study uses a sample of 176 employees consisting of two budget hotels, namely Fave Hotel and RedDoorz using non-probability sampling with a structural equation model approach with SmartPLS 3 software. The results of this study explain that in budget hotels in Indonesia organizational culture and job satisfaction become an important factor in improving employee performance at budget hotels. Leadership style does not have a significant influence on employee performance, but leadership style requires job satisfaction in improving the performance of budget hotel employees. Job satisfaction is also an important factor in budget hotels because several factors that affect employee performance have a significant effect when mediated by job satisfaction.